PRᾹṆᾹYᾹMA DALAM YOGA SURYA DHARYAM SEBAGAI SARANA PERSEMBAHAN DI PASRAMAN SERULING DEWATA - Yogi Swara, I Made Dwipayana; I Made Sugata; I Made Adi Brahman (Pangkaja: Jurnal Agama Hindu, 2026)
ABSTRACT Prāṇāyāma in Surya Dharyam yoga at Pasraman Seruling Dewata is a way to increase spiritual awareness and purify oneself by practicing breathing and performing physical postures (asanas) as a means of worshiping God. This study aims to describe the pranayama techniques in Surya Dharyam yoga, analyze the function of prāṇāyāma in Surya Dharyam yoga, and analyze the influence of prāṇāyāma in Surya Dharyam yoga. This research employed structural functional theory and health theory. The study utilized a qualitative method with an approach based on Edmund Husserl's phenomenology. The data sources were primary and secondary, collected through observation, interviews, literature review, and documentation. The data were analyzed using descriptive qualitative methods. The research findings indicate that pranayama in Yoga Surya Dharyam has an impact on physical, mental, emotional, spiritual, and self-awareness health, as well as on social and relational aspects, lifestyle, and its influence within the context of Yoga Surya Dharyam practice. Therefore, it can be concluded that the implementation of pranayama in Yoga Surya Dharyam contributes a positive influence on various aspects of physical and psychological health for participants of Pasraman Seruling Dewata. The results of this study imply that Yoga Surya Dharyam with pranayama is effective in supporting physical and mental health by enhancing respiratory function, body flexibility, and stress management, making it worthy of integration into healthy lifestyle programs in the community. Keywords: pranayama; yoga surya dharyam.